Flexible energy storage device based on poly(N-phenylglycine), an incentive-energy pseudocapacitive conducting polymer, and electrochemically exfoliated graphite sheets - Muniraj, Vedi Kuyil Azhagan; Boukherroub, Rabah; Shelke, Manjusha Vilas (ACS Sustainable Chemistry & Engineering, 2020)
Poly(N-phenylglycine) (PNPG), an original pseudocapacitive conjugative conducting polymer (CP), was synthesized by the electro-oxidative polymerization method. The synthesis process involves in situ polymerization and electro-deposition of N-phenylglycine onto the surface of highly conductive, few-layered, exfoliated flexible graphite sheets (EFGSs). At first, the promising features of the conjugative structure of the as-prepared protonated PNPG were thoroughly investigated by UV-vis absorption spectrophotometry, micro-Raman spectroscopy, and X-ray photoelectron spectroscopy analysis. The protonated nitrogen groups facilitate the rapid accessibility of counter ions from the electrolyte. Electrochemical studies revealed that the PNPG/E-FGS electrode exhibits an extraordinary areal specific capacitance of 367 mF cm(-2) at 10 mV s(-1). A flexible solid-state symmetrical supercapacitor was further fabricated using PNPG/E-FGS electrodes, exhibiting a specific capacitance as high as 199 mF cm(-2) at 1 mA cm(-2) with an operating voltage of 1.1 V. Furthermore, the device delivered an excellent specific energy of 8.36 mu W h cm(-2) at a power density of 1.65 mW cm(-2) in a working potential window of 1.1 V. More significantly, the energy density was nearly doubled to 16.1 mu W h cm(-2) upon extending the potential window from 1.1 to 1.5 V. The extremely redox-active CP electrode is highly suitable for applications in high-energy electrochemical capacitors with wide operating potential window.
Keywords: conducting polymer; electro-polymerization; exfoliated graphite; flexible supercapacitor; poly(N-phenylglycine)